Malaria (at the Chris Hani/Baragwanath Hospital) : an "alien" epidemic? - Gavalakis, Chrissoula Teresa (My University, 1998)
Despite the efforts, for more than twenty years, to control malaria, the incidence of this disease still appears to be escalating globally. At the Chris Hani/Baragwanath Hospital, data analysis of malaria admissions between January 1994 to December 1996 showed an increasing trend from year to year. The main objective of the study was to try and provide some insight into this increasing rate of malaria at the ChrisHani/Baragwanath Hospital. The study was structured into two main parts: a retrospective analysis which concentrated on malaria admissions between and including January 1994 and March 1994, and a prospective analysis interviewing and examining all the malaria cases that were diagnosed between and including January 1995 and March 1995. Both aspects of the study assessed the patients socioeconomically, haematologically and immunologically. A detailed travel,medical and drug history was taken through the aid of a questionnaire. Two hundred and sixty-three patients (175 male and 88 female), of which 35% (91/263) were children (< 13 years old), were diagnosed with malaria. The clinical and laboratory presentations were consistent with other studies. The prevalence of complicated disease however was less than what has been described in the literature; cerebral malaria (as defined by Warrell, 1982) was documented in 1% of patients, hypoglycaemia (glucose < 2.2 mmol/l) and renal failure (creatinine > 265 umol/l) accounted for 5% and 3% of the cases respectively. In contrast to this 32% had features of liver dysfunction, however it appeared that haemolysis was the main contributing factor to the liver derangement. The most common infecting species was Plasmodium falciparum, alone (91.3% of the patients) or part of a mixed infection with either P. vivax or P.ovale (3.8% of patients). More than 88% of the infections were contracted in other African, mainly southern African countries, the most important of which was neighbouring Mozambique (58%). About 11% were contracted in endemic areas of South Africa i.e Northern Province, Mpumalanga and Kwazulu Natal. Twelve percent of cases (24/203) gave a history of previous malaria, The underlying immune status of these patients was analyzed using the Indirect Fluorescence Antibody Test (IFAT) and compared with the total study group. The test did not reveal any striking differences between the two groups. The previously exposed patients however did demonstrate a much lower parasitaemia, with 71% (17/24) of cases presenting with a parasite density <_;1%. These results may indicate the ability of these patients to clear their parasitaemias earlier due to previous sensitization, with the subsequent establishment of a low grade chronic infection. Seven of 88 women admitted had a documented pregnancy at the time of diagnosis. Foetal death was recorded in 517 cases which confirms the poor prognosis in pregnancy associated malaria infection, reported by other authors. Fifteen patients (13 adults and 2 children) required admission into the intensive care unit. Indications included high parasite loads, > 5% (67%) and renal failure, creatinine> 265 umol/l (33%). Standard chemotherapy was administered to all the patients with the most frequently used being quinine (94% of cases), alone or in combination with other drugs. The use of prophylactic agents for the prevention ofmalaria was restricted to twelve patients (8%), with the majority of individuals being ignorant about( malaria and therefore being unaware that any medication along with other preventative measures, were necessary prior to entering , and while staying in an endemic region. It was also apparent that the correct dosage was not adhered to as none of the patients completed their antimalarial course after returning from the malaria area. The most commonly used prophylactic drugs were chloroquine, alone or in combination with proguanil and pyrimethamine plus dapsone (Maloprim), The latter is no longer recommended routinely as a prophylactic agent. Following univariate analysis using Fisher's exact test and the student t-test, and a multivariate: nalysis (using a logistic regression model), hyperparasitaemia (p=O.0070) and renal failure (p=O.0016) were identified as significant predictors of poor outcome. Significant differences were also demonstrated in the mean WCC and the mean HB levels between the survivors versus the patients that died, indicating that a significantly elevated WCC and an anaemia at presentation, may be important risk factors towards the establishment of severe/complicated infection. The overall mortality rate was 3%. Climatic data (which was limited to the Johannesburg area), together with evidence that the malaria bearing Anopheles vector does not exist in Gauteng suggests that the conditions in the city may not be suitable for local transmission of malaria during the summer. It therefore appears that all efforts need to be channeled into the education of our travelers who visit malaria endemic regions and upon returning succumb to 'imported' malaria. Perhaps the education of the traveler alone is not sufficient, and medical personnel who diagnose the condition and who prescribe prophylactic agents need to revise their knowledge of this life threatening infection, so that their advice and drug therapies are optimal and effective. Lastly the pharmaceutical companies that manufacture these drugs might be persuaded to make their products more affordable for those individuals who are most at risk. We need to utilize our limited options to the fullest until such a time as the ultimate challenge is realised - an effective malaria vaccine.
A dissertation submitted to the Faculty of Medicine, Universlty of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Haematology.
Keywords: Malaria epidemiology.